Epidemiological overview - 18 years of ICU hospitalization due to trauma in Brazil - Maicon Henrique Lentsck; Ana Paula Sayuri Sato; Thais Aidar de Freitas Mathias
ABSTRACT OBJECTIVE Assess the magnitude and trend of hospitalization rates due to traumatic injuries in intensive care units (ICU) in Brazil from 1998 to 2015. METHODS This is an ecological time-series study that analyzed data from the Hospital Information System. A trend analysis of hospitalization rates was performed according to diagnosis, sex and age using generalized linear regression models and Prais-Winsten estimation. RESULTS Rates were higher among male patients, but increased hospitalization due to trauma among female patients influenced the ratio between both sexes. Falls and transport accidents were the most frequent causes of trauma. The average annual growth was 3.6% in ICU trauma hospitalization rates in Brazil, the highest growth was reported in the North region (8%; 95%CI 6.4-9.6), among women (5.4%; 95%CI 4.5-6.3), and among people aged 60 years and older (5.5%; 95%CI, 4.7-6.3). The most frequent causes of trauma are falls (4.5%; 95%CI 3.5-5.5) and care complications (5.4%; 95%CI 4.5-6.3). On the other hand, the annual hospital mortality rate due to trauma in ICU is 1.7% lower, on average (95%CI 2.1-1.3). CONCLUSION An increase in ICU hospitalization rate due to trauma in Brazil may be the result of some factors, such as an increasing number of accidents and cases of violence, the implementation of pre-hospital care, and improved access to care, with more beds in ICU. In addition, population aging is another factor, as a greater increase in hospitalization was observed among people aged 60 years and older.